Dolly all the time - Monaghan, Annabel (Good morning America book club., 2026)
"If they start by pretending, can they end with something real? Dolly Brick has never met a problem she couldn't solve. Not when her mom left when she was twelve, and not at thirty-nine when she moves with her son back to Whitfield, Rhode Island for the summer to keep her dad and brother from losing the family home. So when she comes across Stewart Whitfield: annoyingly handsome scion of the Whitfield family: with a flat tire and at the wrong end of a very public, very humiliating breakup, it's in her nature to help. But Stewart's proposed arrangement ends up being more than either of them bargained for, because as public dinners and high society benefits turn into sunset boat rides and kisses that hit her bloodstream like a ghost pepper, Dolly starts to feel something more than helpful. She's never relied on anyone besides herself, can she really start now?"--